Novel mutations in DNAJB6 cause LGMD1D and distal myopathy in French families. (30th March 2018) - Jonson, P. H.; Palmio, J.; Johari, M.; Penttilä, S.; Evilä, A.; Nelson, I.; Bonne, G.; Wiart, N.; Meyer, V.; Boland, A.; Deleuze, J.‐F.; Masson, C.; et al.
Abstract : Background and purpose: The aim was to determine the genetic background of unknown muscular dystrophy in five French families. Methods: Twelve patients with limb girdle muscular dystrophy or distal myopathy were clinically evaluated. Gene mutations were identified using targeted exon sequencing and mutated DNAJB6 was tested in vitro . Results: Five patients presented with distal lower limb weakness whilst others had proximal presentation with a variable rate of progression starting at the mean age of 38.5 years. Two novel mutations (c.284A>T, p.Asn95Ile, two families; and c.293_295delATG, p.Asp98del, one family) as well as the previously reported c.279C>G (p.Phe93Leu, two families) mutation in DNAJB6 were identified. All showed a reduced capacity to prevent protein aggregation. Conclusions: The mutational and phenotypical spectrum of DNAJB6 ‐caused muscle disease is larger than previously reported, including also dysphagia. The originally reported c.279C>G (p.Phe93Leu) mutation is now identified in four different populations and appears to be a mutational hotspot. Our report confirms that some DNAJB6 mutations cause distal‐onset myopathy and hence DNAJB6 defects should be considered broadly in dominant muscular dystrophy families.